Analysis of Work Ability on Employee Performance at the Makassar District Office in Makassar - Lukman S (Universitas Dharma Wacana, 2022)
The purpose of this research is to examine work ability in terms of work discipline, work drive, and information technology. Work ability is a condition that exists in employees who are efficient and competent in their assigned sector of work. Employee ability is determined by potential, and intellectual ability is intelligence. A systematic review was utilized in this study to examine reviews of clearly articulated issues that employed explicit and orderly strategies to find, select, and basically evaluate applicable examination, as well as accumulate and break down information from the included investigations. Information was accumulated from 53 sources connected with the examination of functionality. As indicated by the discoveries of the exploration, the ability to deal with work discipline, work motivation, and technological mastery is in line with the needs needed to increase employee performance at the Makassar District Office in Makassar City, South Sulawesi District.